POTENTIAL FOR THE APPLICATION OF SUGAR CANE BAGASSE AND RICE IN THE REMOVAL OF CONTAMINANTS PRESENT IN THE WATER PRODUCED OF PETROLEUM - Mayra Almeida Cavalcante; Leila Maria de Melo Marques; Fernando Dantas de Santana Junior; Kilton Renan Alves Pereira; Keila Regina Santana Fagundes; Fábio Pereira Fagundes (The Journal of Engineering and Exact Sciences)
Despite the huge advances made in the petroleum sector regarding the innovation of its technological processes, there are still some troubling problems. An example of this refers to the water produced. Treatment and disposal has become one of the biggest challenges in the oil industry. The problem consists in the difficulty of degradation of the compounds to an adequate level that allows the safe disposal in the environment, ensuring the possibility of reuse or disposal in the standards established by the environmental agencies. This fact has encouraged researchers to direct studies to find alternatives capable of efficiently removing the contaminants present in this water at a lower cost compared to other existing technologies. Thus, the purpose of this work is to use adsorbent materials with high porosity and high silica content, such as sugarcane bagasse and rice, in order to remove the crude oil content present in the water produced. The adsorption process of the crude oil on the surface of each support occurred at predetermined intervals and with different concentrations of contaminant and adsorbent. A factorial modeling mapping (3²) was performed to evaluate the effect of the interactions between the concentrations of each support in relation to the contaminant. From the results obtained, it was verified that the calcination of sugarcane bagasse and rice was fundamental for the efficiency of the system. In all the systems an increase of the percentage of removal using these adsorbents was observed, suggesting that both represent a promising application in the advance of technologies responsible for the treatment of the water produced.